Fluorine-containing ether compound, lubricant for magnetic recording medium, and magnetic recording medium
A fluorine-containing ether compound with a specific terminal group addresses the challenge of maintaining lubricant layer coverage and resistance in magnetic recording media, ensuring reliable and durable performance even at reduced thickness.
Patent Information
- Application Number
- JP2021550518
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2020-09-08
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-09-08
AI Technical Summary
Magnetic recording media face challenges in achieving reduced flying height of the magnetic head while maintaining sufficient lubricant layer coverage, chemical resistance, and wear resistance, especially when the lubricant layer thickness is reduced.
A fluorine-containing ether compound with a specific terminal group containing two or three polar groups bonded via a perfluoropolyether chain, which enhances adhesion and interaction with the protective layer, providing excellent chemical resistance and wear resistance even at reduced thickness.
The fluorine-containing ether compound forms a lubricant layer with high coverage and excellent chemical resistance and wear resistance, preventing aggregation and adherence to the magnetic head, thus ensuring reliable and durable magnetic recording media.
Smart Images

Figure 0007619269000040 
Figure 0007619269000001 
Figure 0007619269000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a fluorine-containing ether compound, a lubricant for a magnetic recording medium, and a magnetic recording medium. This application claims priority based on Japanese Patent Application No. 2019-179774, filed on September 30, 2019, the contents of which are incorporated herein by reference. [Background technology]
[0002] In order to improve the recording density of magnetic recording and reproducing devices, development of magnetic recording media suitable for high recording density is underway. Conventionally, magnetic recording media include those in which a recording layer is formed on a substrate and a protective layer such as carbon is formed on the recording layer. The protective layer protects the information recorded on the recording layer and also improves the sliding properties of the magnetic head. However, the durability of the magnetic recording medium cannot be sufficiently obtained by simply providing a protective layer on the recording layer. For this reason, a lubricant is generally applied to the surface of the protective layer to form a lubricating layer.
[0003] As lubricants for use in forming a lubricating layer on a magnetic recording medium, for example, those containing a compound having a polar group such as a hydroxy group or an amino group at the end of a fluorine-based polymer having a repeating structure containing CF2 have been proposed. For example, Patent Document 1 discloses a fluoropolyether compound having an amino alcohol group at the molecular end. Patent Document 2 discloses a fluorine-containing ether compound in which a group having a heterocycle is bonded to both ends of a perfluoropolyether chain via a divalent linking group having a polar group. Patent Document 3 discloses a fluoroether compound having an amino group having a hydroxyl group at both ends of the molecule. Patent Document 4 discloses a perfluoropolyether liquid lubricant having an amine functional group at at least one end of a chain molecule. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-131083 [Patent Document 2] International Publication No. 2018 / 139174 [Patent Document 3] JP 2006-225572 A [Patent Document 4] Patent No. 4099860 Summary of the Invention [Problem to be solved by the invention]
[0005] In magnetic recording and reproducing devices, there is a demand for an even smaller flying height of the magnetic head, which in turn requires a thinner lubricating layer in the magnetic recording medium. However, generally, when the thickness of the lubricating layer is reduced, the covering property of the lubricating layer decreases, and the chemical resistance and wear resistance of the magnetic recording medium tend to decrease.
[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a fluorine-containing ether compound suitable as a material for a lubricant for a magnetic recording medium, which is capable of forming a lubricating layer having excellent chemical resistance and abrasion resistance even when the thickness is reduced. Another object of the present invention is to provide a lubricant for magnetic recording media which contains the fluorinated ether compound of the present invention and is capable of forming a lubricating layer having excellent chemical resistance and abrasion resistance. Another object of the present invention is to provide a magnetic recording medium having excellent reliability and durability, which is provided with a lubricating layer containing the fluorinated ether compound of the present invention. [Means for solving the problem]
[0007] The present inventors have conducted extensive research in order to solve the above problems. As a result, the present inventors found that a fluorine-containing ether compound having a perfluoropolyether chain, a group containing a tertiary amine bonded to a first end of the perfluoropolyether chain via a methylene group and a specific linking group, and a specific terminal group containing two or three polar groups bonded to a second end via a methylene group would be sufficient, and thus arrived at the present invention. That is, a first aspect of the present invention is the following fluorine-containing ether compound.
[0008] [1] A fluorinated ether compound represented by the following formula (1): R 1 -R 2 -CH2-R 3 -CH2-R 4 (1) (In formula (1), R 3 is a perfluoropolyether chain; R 1 is represented by the following formula (2), in which a is an integer of 2 or 3, and in formula (2), R 5 and R 6 are the same or different substituents, R 5 and R 6 may form a ring structure together with the nitrogen atom; R 2 is represented by the following formula (3), where b in formula (3) is an integer of 1 to 3; 4 is an end group containing two or three polar groups, each polar group being bonded to a different carbon atom, and the carbon atoms to which the polar groups are bonded being bonded to each other via a linking group containing a carbon atom to which no polar group is bonded.
[0009] [ka]
[0010] The fluorine-containing ether compound according to the first aspect of the present invention can preferably include the following characteristics, as described below. Two or more of the following characteristics may be preferably combined. [2] R 5 and R 6are each independently a saturated aliphatic group having 1 to 4 carbon atoms, or 5 and R 6
[0025] 3. The fluorine-containing ether compound according to [1], wherein [3] R in the above formula (2) 5 R 6 The fluorine-containing ether compound according to [1], wherein N- is a dimethylamino group or a diethylamino group. [4] R in the above formula (2) 5 R 6 The fluorine-containing ether compound according to [1], wherein N- is any one group selected from a pyrrolidine group, a piperidine group, a morpholine group and a hexamethyleneimine group.
[0011] [5] R 3 is any one of the following formulae (4) to (6): -CF2O-(CF2CF2O) c -(CF2O) d -CF2- (4) (In formula (4), c and d each represent an average degree of polymerization and are 0 to 30. However, c and d cannot be 0 at the same time.) -CF(CF3)-(OCF(CF3)CF2) e -OCF(CF3)- (5) (In formula (5), e represents the average degree of polymerization and is from 0.1 to 30.) -CF2CF2O-(CF2CF2CF2O) f -CF2CF2- (6) (In formula (6), f represents the average degree of polymerization and is 0.1 to 30.)
[0012] [6] R 4 The fluorine-containing ether compound according to any one of [1] to [5], wherein the polar group is a hydroxyl group. [7] R 4 is a terminal group represented by any one of the following formulae (7) to (10):
[0013] [ka] (In formula (7), g represents an integer of 1 to 2, and h represents an integer of 1 to 5.) (In formula (8), i represents an integer of 2 to 5.) (In formula (9), j represents an integer of 1 to 5.) (In formula (10), k represents an integer of 1 or 2, and l represents an integer of 1 or 2.)
[0014] [8] The fluorinated ether compound according to any one of [1] to [7], having a number average molecular weight in the range of 500 to 10,000. [9] The fluorinated ether compound according to any one of [1] to [8], wherein the compound represented by formula (1) is any one of the compounds represented by the following formulae (A) to (D), (N) and (O):
[0015] [ka] (In formula (A), ma and na represent average degrees of polymerization, ma represents 1 to 30, and na represents 0 to 30.) (In the formula (B), mb and nb represent average degrees of polymerization, mb represents 1 to 30, and nb represents 0 to 30.) (In formula (C), mc and nc represent average degrees of polymerization, mc represents 1 to 30, and nc represents 0 to 30.) (In formula (D), md and nd represent average degrees of polymerization, md represents 1 to 30, and nd represents 0 to 30.) (In the formula (N), mn and nn represent average degrees of polymerization, mn represents 1 to 30, and nn represents 0 to 30.) (In formula (O), mo and no represent average degrees of polymerization, mo represents 1 to 30, and no represents 0 to 30.)
[0016]
[10] A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of [1] to [9].
[0017]
[11] A magnetic recording medium comprising at least a magnetic layer, a protective layer, and a lubricating layer provided in that order on a substrate, 2. A magnetic recording medium, wherein the lubricating layer contains the fluorine-containing ether compound according to any one of [1] to [9].
[12] The magnetic recording medium according to
[11] , wherein the average thickness of the lubricating layer is 0.5 nm to 2 nm. Effect of the Invention
[0018] The fluorine-containing ether compound of the present invention is a compound represented by the above formula (1), and is suitable as a material for a lubricant for a magnetic recording medium. Since the lubricant for magnetic recording media of the present invention contains the fluorine-containing ether compound of the present invention, it is possible to form a lubricating layer that has excellent chemical resistance and abrasion resistance even if it is thin. The magnetic recording medium of the present invention has excellent reliability and durability because it is provided with a lubricating layer which contains the fluorinated ether compound of the present invention and has excellent chemical resistance and abrasion resistance. [Brief description of the drawings]
[0019] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a magnetic recording medium of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Preferred examples of the fluorine-containing ether compound, the lubricant for magnetic recording media (hereinafter sometimes abbreviated as "lubricant"), and the magnetic recording media of the present invention will be described in detail below. The present invention is not limited to the following embodiments. Within the scope of the present invention, the number, position, type, amount, ratio, combination, numerical value, size, etc. can be omitted, changed, and / or added as necessary.
[0021] [Fluorine-containing ether compounds] The fluorine-containing ether compound of the present embodiment is represented by the following formula (1). R 1 -R2 -CH2-R 3 -CH2-R 4 (1) (In formula (1), R 3 is a perfluoropolyether chain. 1 is represented by the following formula (2). In formula (2), a is an integer of 2 or 3. In formula (2), R 5 and R 6 are the same or different substituents, R 5 and R 6 R may form a ring structure together with the nitrogen atom. 2 is represented by the following formula (3). In formula (3), b is an integer of 1 to 3. 4 is an end group containing two or three polar groups, each polar group being bonded to a different carbon atom, and the carbon atoms to which the polar groups are bonded being bonded to each other via a linking group containing a carbon atom to which no polar group is bonded.
[0022] [ka]
[0023] (R 1 )) In the fluorine-containing ether compound represented by formula (1), R 1 is a group represented by formula (2), and a tertiary amine (R 5 R 6 The unshared electron pair of the nitrogen atom forming the tertiary amine is presumed to exhibit good interaction with the protective layer in the lubricating layer containing the fluorine-containing ether compound represented by formula (1), to increase the adhesive force to the protective layer and to improve the chemical resistance and wear resistance of the lubricant.
[0024] R 1 The nitrogen atom of the tertiary amine contained in the alkylene group (-(CH2) a -) in formula (2). a-O- is a divalent linking group having an ether bond, and a in formula (2) is an integer of 2 or 3. Therefore, in the fluorine-containing ether compound represented by formula (1), the nitrogen atom in the tertiary amine and R 2 The distance between the hydroxyl group (-OH) in the formula (2) is considered to be appropriate. If a in formula (2) is 1 or 0, the resulting fluorine-containing ether compound is prone to intramolecular aggregation. As a result, if the thickness of the lubricating layer containing this is reduced, sufficient coverage cannot be obtained, and sufficient chemical resistance and wear resistance cannot be obtained. In addition, if a in formula (2) exceeds 3, the alkylene group becomes too long, increasing the mobility of the molecular end, making it difficult to obtain the adsorption force of the tertiary amine to the protective layer.
[0025] The fluorine-containing ether compound represented by formula (1) is unlikely to undergo intramolecular aggregation in the lubricating layer containing it, since a in formula (2) is an integer of 2 or 3, and is likely to be arranged in a state in which it spreads uniformly in the surface direction on the protective layer. Therefore, even if the lubricant containing the fluorine-containing ether compound represented by formula (1) is thin, it can cover the surface of the protective layer with a high coverage rate and form a lubricating layer with excellent chemical resistance and wear resistance. a in formula (2) is the nitrogen atom in the tertiary amine and R 2 In order to obtain a more appropriate distance between the hydroxyl group (-OH) and the aryl group, it is preferable that the number is 2.
[0026] In the fluorine-containing ether compound represented by formula (1), the ether bond (-O-) in formula (2) forms R 1 R 2 The molecular structure has moderate flexibility because the lubricating layer containing the fluorine-containing ether compound represented by formula (1) has R 1 and R 2 When the lubricating layer contains a fluorine-containing ether compound, the lubricating layer exhibits good interaction with the protective film disposed in contact with the lubricating layer. Therefore, the lubricating layer containing the fluorine-containing ether compound is easily adsorbed to the protective layer, has excellent adhesion to the protective layer, and exhibits excellent chemical resistance and abrasion resistance.
[0027] In the fluorine-containing ether compound represented by formula (1), the structure of the tertiary amine contained in formula (2) can be appropriately selected depending on the performance required of a lubricant containing the fluorine-containing ether compound. R in Equation (2) 5 and R 6 are the same or different substituents. Examples of the substituents include linear, branched, or cyclic saturated aliphatic groups, and linear, branched, or cyclic unsaturated aliphatic groups. R 5 and R 6 may form a ring structure together with the nitrogen atom.
[0028] R 1 The tertiary amine contained in is an acyclic amine (R 5 and R 6 does not form a ring structure together with the nitrogen atom), the tertiary amine (R 5 R 6Specific examples of N-) include, for example, a dimethylamino group, a diethylamino group, a dipropylamino group, a diisopropylamino group, a di-n-butylamino group, a diisobutylamino group, a di-sec-butylamino group, a di-tert-butylamino group, an ethylmethylamino group, a n-propylmethylamino group, an isopropylmethylamino group, a n-butylmethylamino group, an isobutylmethylamino group, a sec-butylmethylamino group, a tert-butylmethylamino group, an ethyln-propylamino group, an ethylisopropylamino group, an ethyln-butylamino group, an ethylisobutylamino group, a sec-butylethylamino group, a tert-butylethylamino group, an isopropylpropylamino group, Examples of such groups include a n-butylpropylamino group, a n-butylpropylamino group, a (2-methylpropyl)(propyl)amino group, an N-sec-butylpropylamino group, an N-tert-butylpropylamino group, an N-(1-methylethyl)-1-butylamino group, an N-isopropyl-2-methyl-1-propylamino group, an N-(1-methylethyl)-2-butylamino group, an N-isopropyl-2-methyl-2-propylamino group, a butylisobutylamino group, a butyl-sec-butylamino group, a butyl-tert-butylamino group, an N-(2-methylpropyl)-2-butylamino group, an N-(1,1-dimethylethyl)-2-methylpropylamino group, and an N-(1,1-dimethylethyl)-2-butylamino group.
[0029] R 1 The tertiary amine contained in is an acyclic amine (R 5 and R 6 does not form a ring structure with the nitrogen atom), R 5 and R 6 are preferably each independently a saturated aliphatic group having 1 to 4 carbon atoms. In this case, R 5 R 6N- has a moderate bulkiness, and thus the fluorine-containing ether compound has a moderate steric hindrance and mobility.When the lubricating layer containing such a fluorine-containing ether compound is disposed on the protective layer, it is presumed that the lubricating layer functions as a cushion (a buffer material having elasticity) that absorbs the impact caused by the collision of the magnetic head with the protective layer.This prevents the magnetic head from approaching too close to the protective layer, and the distance between the magnetic head and the protective layer is kept appropriate.As a result, the lubricating layer containing such a fluorine-containing ether compound has good affinity with the protective layer and excellent wear resistance.
[0030] Examples of the saturated aliphatic group having 1 to 4 carbon atoms include a methyl group, an ethyl group, a normal propyl group, an isopropyl group, a normal butyl group, an isobutyl group, a sec-butyl group, and a tert-butyl group. Among these, a saturated aliphatic group having 1 to 2 carbon atoms is preferable. Specifically, R 5 and R 6 are each preferably independently a methyl group or an ethyl group, and R 5 and R 6 It is more preferable that R 1 When the tertiary amine contained in the formula (2) is a non-cyclic amine, 5 R 6 N- is preferably any one of groups selected from a dimethylamino group, a methylethylamino group, and a diethylamino group, and is more preferably a dimethylamino group or a diethylamino group because of ease of synthesis.
[0031] R 1 The tertiary amine contained in is a cyclic amine (R 5 and R 6 forms a ring structure together with the nitrogen atom), the tertiary amine (R 5 R 6 Specific examples of N-) include an ethyleneimine group, an azacyclobutane group, a pyrrolidine group, a piperidine group, a morpholine group, a hexamethyleneimine group, a heptamethyleneimine group, and an octamethyleneimine group.
[0032] R 1 The tertiary amine contained in is a cyclic amine (R 5 and R 6 When R forms a ring structure together with the nitrogen atom, the cyclic amine may have a substituent. Specific examples of the substituent include an alkyl group having 1 to 3 carbon atoms and a polar group. 1 When the cyclic amine contained in has a substituent containing a polar group, examples of the polar group include a hydroxyl group, an amino group, a carboxyl group, etc., and a hydroxyl group is preferable. The bonding position of the substituent in the cyclic amine having a substituent is not particularly limited, and the substituent may be bonded to any carbon atom constituting the cyclic amine. R 5 and R 6 When forms a ring structure together with the nitrogen atom, the ring structure may contain a heteroatom other than the nitrogen atom of the tertiary amine. Examples of the heteroatom other than the nitrogen atom of the tertiary amine include an oxygen atom and / or a nitrogen atom.
[0033] R 1 When the tertiary amine contained in R is a cyclic amine, 5 and R 6 It is preferable that R in formula (2) forms a 5- to 7-membered ring together with the nitrogen atom. 5 R 6 Since N- has a suitable bulkiness, the fluorine-containing ether compound has a suitable steric hindrance and mobility. As a result, the lubricating layer containing this has a good affinity with the protective layer and has excellent wear resistance. Specifically, R 5 R 6 It is preferable that N- is any one group selected from a pyrrolidine group, a piperidine group, a morpholine group, and a hexamethyleneimine group. 5 R 6 When N- is a pyrrolidine group or a morpholine group, a lubricating layer having excellent abrasion resistance can be obtained, which is preferable.
[0034] (R2 )) In the fluorine-containing ether compound represented by formula (1), a group represented by formula (2) (R 1 ) and R 3 Between the perfluoropolyether chain represented by formula (3), a divalent linking group (R 2 ) is arranged. 2 ) contains 1 to 3 hydroxyl groups (-OH) which are polar groups. As a result, in the lubricating layer containing the fluorine-containing ether compound of this embodiment, a good interaction occurs between the lubricating layer and the protective layer, and excellent adhesion (adhesion) to the protective layer is obtained. In addition, the linking group (R 2 ) contains an ether bond (-O-), and therefore provides appropriate flexibility to the molecular structure of the fluorinated ether compound represented by formula (1). For these reasons, the fluorinated ether compound of the present embodiment can be, for example, 1 and R 3 In comparison with a fluorine-containing ether compound in which the groups are directly bonded, a lubricating layer containing this compound is more likely to adhere to a protective film, and the adhesion between the lubricating layer and the protective layer is excellent.
[0035] In formula (3), b is an integer of 1, 2, or 3. Since b in formula (3) is 1 or more, when a lubricating layer is formed on a protective layer using a lubricant containing a fluorine-containing ether compound shown in formula (1), R 2 The lubricating layer containing the fluorine-containing ether compound represented by formula (1) easily adheres to the protective layer, and has excellent adhesion to the protective layer, chemical resistance, and abrasion resistance. When b in formula (3) is 2 or more, R 2 The interaction between the hydroxyl group of R and the protective layer is improved, and the adhesion to the protective layer is improved. 2 The polarity of the fluorine-containing ether compound does not become too high due to the presence of too many hydroxyl groups. Therefore, it is possible to prevent the lubricating layer containing the fluorine-containing ether compound from adhering to the magnetic head as a foreign matter (smear) due to the polarity of the fluorine-containing ether compound being too high, and pickup can be suppressed. 2is expressed by formula (3), so when a is 2 or 3, R 2 The hydroxyl groups contained in the compound are arranged at an appropriate distance from each other.
[0036] (R 3 (perfluoropolyether chain represented by In the fluorine-containing ether compound represented by formula (1), R 3 is a perfluoropolyether chain (hereinafter, sometimes abbreviated as "PFPE chain"). When a lubricant containing the fluorine-containing ether compound of this embodiment is applied onto a protective layer to form a lubricating layer, the PFPE chain covers the surface of the protective layer and imparts lubricity to the lubricating layer, thereby reducing the frictional force between the magnetic head and the protective layer. The PFPE chain is appropriately selected depending on the performance required of the lubricant containing the fluorine-containing ether compound. In the fluorine-containing ether compound represented by formula (1), the molecule contains only one PFPE chain (R 3 When the molecule contains one PFPE chain, R 1 and R 4 does not contain a PFPE chain.
[0037] Examples of PFPE chains include those made of perfluoromethylene oxide polymers, perfluoroethylene oxide polymers, perfluoro-n-propylene oxide polymers, and perfluoroisopropylene oxide polymers, those based on these polymers, and those made of copolymers of the monomers that constitute these polymers.
[0038] Specifically, R in formula (1) 3 is preferably represented by any one of the following formulas (4) to (6). 3 When R is any one of the formulas (4) to (6), the fluorine-containing ether compound can be easily synthesized. 3 is formula (4), it is more preferable since the raw materials are easily available. Also, R 3When R is any one of the formulas (4) to (6), the ratio of the number of oxygen atoms (the number of ether bonds (-O-)) to the number of carbon atoms in the perfluoropolyether chain is appropriate. This results in a fluorine-containing ether compound with appropriate hardness. Therefore, the fluorine-containing ether compound applied onto the protective layer is less likely to aggregate on the protective layer, and a thinner lubricating layer can be formed with a sufficient coverage. In addition, R 3 When is any one of the formulas (4) to (6), the fluorine-containing ether compound provides a lubricating layer having good wear resistance.
[0039] -CF2O-(CF2CF2O) c -(CF2O) d -CF2- (4) (In formula (4), c and d each represent an average degree of polymerization and are 0 to 30. However, c and d cannot be 0 at the same time.)
[0040] In formula (4), the arrangement order of the repeating units (CF2-CF2-O) and (CF2-O) is not particularly limited. In formula (4), the number c of (CF2-CF2-O) and the number d of (CF2-O) may be the same or different. However, c and d cannot be 0 at the same time. Formula (4) may include any of a random copolymer, a block copolymer, and an alternating copolymer composed of monomer units (CF2-CF2-O) and (CF2-O).
[0041] In formula (4), c indicating the average degree of polymerization is 0 to 30, preferably 1 to 20, and more preferably 3 to 10. In formula (4), d indicating the average degree of polymerization is 0 to 30, preferably 1 to 20, and more preferably 3 to 10.
[0042] -CF(CF3)-(OCF(CF3)CF2) e -OCF(CF3)- (5) (In formula (5), e represents the average degree of polymerization and is from 0.1 to 30.) In the formula (5), e representing the average degree of polymerization is 0.1 to 30, preferably 1 to 30, more preferably 2 to 20, and further preferably 3 to 10.
[0043] -CF2CF2O-(CF2CF2CF2O) f -CF2CF2- (6) (In formula (6), f represents the average degree of polymerization and is 0.1 to 30.) In formula (6), f representing the average degree of polymerization is 0.1 to 30, preferably 1 to 30, more preferably 2 to 20, and further preferably 3 to 10.
[0044] When c, d, e and f, which indicate the average polymerization degrees in the formulas (4) to (6), are 30 or less, the viscosity of the fluorinated ether compound does not become too high, and the lubricant containing it becomes easy to apply, which is preferable.
[0045] (R 4 (Terminal group represented by In the fluorine-containing ether compound represented by formula (1), R 4 is a terminal group containing two or three polar groups, each of which is bonded to a different carbon atom, and the carbon atoms to which the polar groups are bonded are bonded via a linking group containing a carbon atom to which no polar group is bonded. 4 It is preferable that the end group represented by the following formula (I) does not contain a perfluoropolyether chain (PFPE chain). R 4 The terminal group represented by the following formula contributes to the adhesion between the protective layer to which the lubricant containing the fluorinated ether compound of this embodiment is applied and the lubricating layer formed by applying the lubricant.
[0046] R 4 Since the number of polar groups contained in R is two or three, the lubricant containing the fluorine-containing ether compound has excellent adhesion to the protective layer and can form a lubricating layer with a high coverage. 4If the number of polar groups contained in R is too large, the polarity of the fluorine-containing ether compound becomes too high, and the lubricating layer containing the fluorine-containing ether compound is likely to adhere to the magnetic head as a foreign matter (smear), resulting in pickup. 4 Since the number of polar groups contained in the compound is 2 or 3, the occurrence of pick-up due to the fluorine-containing ether compound having too high a polarity can be suppressed.
[0047] R 4 The fluorine-containing ether compound having an end group represented by is less likely to aggregate than a fluorine-containing ether compound in which the two polar groups contained in the end group are bonded to different carbon atoms, and the carbon atoms to which the polar groups are bonded are bonded to each other. Therefore, in the lubricating layer containing the fluorine-containing ether compound of this embodiment, the fluorine-containing ether compound that is not in close contact (adsorbed) with the protective layer can be prevented from aggregating and adhering to the magnetic head as a foreign matter (smear), and pickup is suppressed. In addition, since the fluorine-containing ether compounds are less likely to aggregate with each other, the fluorine-containing ether compound in the lubricating layer is likely to be arranged in a state in which it spreads and extends in the surface direction on the protective layer. Therefore, it is presumed that the lubricant containing the above-mentioned fluorine-containing ether compound can cover the surface of the protective layer with a high coverage rate even if the thickness is reduced, and can form a lubricating layer with excellent chemical resistance and wear resistance.
[0048] R 4 Examples of the two or three polar groups in the terminal group represented by the formula (I) include a hydroxyl group (-OH), an amino group (-NH2), a carboxyl group (-COOH), and a mercapto group (-SH). Note that an ether bond (-O-) is represented by the formula (I). 4 Among the above polar groups, the polar group is preferably a hydroxyl group. 4 The two or three polar groups contained in the terminal group represented by the formula (I) may be different from each other or may all be the same, and it is preferable that all of them are hydroxyl groups.
[0049] Hydroxyl groups have a strong interaction with protective layers, especially those made of carbon-based materials.4 When some or all of the two or three polar groups in the terminal group represented by the formula (I) are hydroxyl groups, the lubricating layer containing the fluorine-containing ether compound has even higher adhesion to the protective film, which is preferable.
[0050] R in formula (1) 4 can be appropriately selected depending on the performance required for the lubricant containing the fluorine-containing ether compound. 4 is preferably a terminal group represented by any one of the following formulas (7) to (10).
[0051] [ka] (In formula (7), g represents an integer of 1 to 2, and h represents an integer of 1 to 5.) (In formula (8), i represents an integer of 2 to 5.) (In formula (9), j represents an integer of 1 to 5.) (In formula (10), k represents an integer of 1 or 2, and l represents an integer of 1 or 2.)
[0052] In formula (7), g is an integer of 1 to 2. When g in formula (7) is 2, R 2 This is preferable because the adhesion to the protective layer is improved due to the interaction between the hydroxyl group of the compound and the protective layer. In formula (7), h is an integer of 1 to 5. In this case, the distance between hydroxyl groups in the terminal group represented by formula (7) becomes appropriate, resulting in a fluorine-containing ether compound that is excellent in adhesion to a protective layer and can form a lubricating layer with a high coverage. h is preferably 1 to 2, and most preferably 1.
[0053] In formula (8), i is an integer from 2 to 5. In this case, R 3 The distance between the side hydroxyl group and the terminal hydroxyl group becomes appropriate, resulting in a fluorine-containing ether compound capable of forming a lubricating layer having excellent adhesion to a protective layer and a high coverage.
[0054] In formula (9), j is an integer from 1 to 5. In this case, R 3 The distance between the side hydroxyl group and the terminal hydroxyl group becomes appropriate, resulting in a fluorine-containing ether compound capable of forming a lubricating layer having excellent adhesion to a protective layer and a high coverage.
[0055] In formula (10), k represents an integer of 1 to 2, and l represents an integer of 1 to 2. When k is an integer of 1 to 2 and l is an integer of 1 to 2, R 3 The distance between the side hydroxyl group and the terminal hydroxyl group becomes appropriate, resulting in a fluorine-containing ether compound that is excellent in adhesion to a protective layer and can form a lubricating layer with a high coverage. k is preferably 2. l is preferably 1.
[0056] Specifically, the fluorine-containing ether compound represented by formula (1) is preferably a compound represented by the following formulae (A) to (R). Among these, any of the compounds represented by formulae (E) and (G) to (M) is preferred, as they have particularly excellent chemical resistance and abrasion resistance. In addition, the compounds represented by formulae (A) to (D), (N) and (O) are all R 2 is represented by formula (3), b in formula (3) is 1, and R 3 is a PFPE chain represented by formula (4), and R 4 is represented by formula (7), and g and h in formula (7) are 1. For this reason, the compounds represented by formulas (A) to (D), (N) and (O) are preferred because they are easy to synthesize. The repeat numbers represented by ma through mp and na through np in formulas (A) to (P), mq in formula (Q), and mr in formula (R) are values indicating the average degree of polymerization, and therefore are not necessarily integers.
[0057] The compounds represented by the following formulas (A) to (P) are all R 3 is the PFPE chain represented by the above formula (4). The compounds represented by the following formulas (A) to (H) are all R 2 is expressed by equation (3), where b is 1. The compounds represented by the following formulas (A) to (D) are all R 4 is expressed by equation (7), where g and h are 1.
[0058] The compound represented by the following formula (A) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a pyrrolidine group. In formula (2), a is 2. The compound represented by the following formula (B) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a piperidine group. In formula (2), a is 2. The compound represented by the following formula (C) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a morpholine group. In formula (2), a is 2. The compound represented by the following formula (D) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a hexamethyleneimine group. In formula (2), a is 2.
[0059] The compounds represented by the following formulas (E) to (H) are all R 4 is expressed by equation (7), where g is 2 and h is 1. The compound represented by the following formula (E) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a pyrrolidine group. In formula (2), a is 2. The compound represented by the following formula (F) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a piperidine group. In formula (2), a is 2. The compound represented by the following formula (G) is R 1 is a group represented by formula (2), and R5 R 6 N- is a morpholine group. In formula (2), a is 2. The compound represented by the following formula (H) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a hexamethyleneimine group. In formula (2), a is 2.
[0060] The compounds represented by the following formulas (I) to (M) are all R 2 is expressed by equation (3), where b is 2. The compounds represented by the following formulas (I) to (L) are all R 4 is expressed by equation (7), where g is 2 and h is 1.
[0061] The compound represented by the following formula (I) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a pyrrolidine group. In formula (2), a is 2. The compound represented by the following formula (J) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a piperidine group. In formula (2), a is 2. The compound represented by the following formula (K) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a morpholine group. In formula (2), a is 2. The compound represented by the following formula (L) is R 1 is a group represented by formula (2), and R 5 R 6 N- is a hexamethyleneimine group. In formula (2), a is 2.
[0062] The compound represented by the following formula (M) is R 4 is represented by formula (10), where k is 2 and l is 1. The compound represented by the following formula (M) is1 is a group represented by formula (2), and R 5 R 6 N- is a pyrrolidine group. In formula (2), a is 3.
[0063] The compounds represented by the following formulas (N) and (O) are both R 2 is represented by formula (3), and b in formula (3) is 1. The compounds represented by the following formulas (N) and (O) are both R 4 is represented by formula (7), and g and h in formula (7) are 1. The compounds represented by the following formulas (N) and (O) are both R 1 is a group represented by formula (2), and R 5 R 6 N- is a dimethylamino group. In the compound represented by the following formula (N), a in formula (2) is 2. In the compound represented by the following formula (O), a in formula (2) is 3.
[0064] The compound represented by the following formula (P) is R 2 is represented by formula (3), and b in formula (3) is 2. The compound represented by the following formula (P) is 4 is represented by formula (7), and g and h in formula (7) are 1. The compound represented by the following formula (P) is 1 is a group represented by formula (2), and R 5 R 6 N- is a diethylamino group. a in formula (2) is 2.
[0065] The compounds represented by the following formulas (Q) and (R) are 4 is expressed by equation (7), where g and h are 1. The compound represented by the following formula (Q) is R 3 is a PFPE chain represented by formula (4). The compound represented by the following formula (Q) is 2 is represented by formula (3), and b in formula (3) is 1. The compound represented by the following formula (Q) is 1 is a group represented by formula (2), and R 5 R 6N- is a pyrrolidine group. In formula (2), a is 2. The compound represented by the following formula (R) is R 3 is a PFPE chain represented by formula (6). The compound represented by the following formula (R) is 2 is represented by formula (3), and b in formula (3) is 1. The compound represented by the following formula (R) is 1 is a group represented by formula (2), and R 5 R 6 N- is a pyrrolidine group. In formula (2), a is 2.
[0066] [ka] (In formula (A), ma and na represent average degrees of polymerization, ma represents 1 to 30, and na represents 0 to 30.) (In the formula (B), mb and nb represent average degrees of polymerization, mb represents 1 to 30, and nb represents 0 to 30.) (In formula (C), mc and nc represent average degrees of polymerization, mc represents 1 to 30, and nc represents 0 to 30.) (In formula (D), md and nd represent average degrees of polymerization, md represents 1 to 30, and nd represents 0 to 30.)
[0067] [ka] (In formula (E), me and ne represent average degrees of polymerization, where me represents 1 to 30 and ne represents 0 to 30.) (In formula (F), mf and nf represent average degrees of polymerization, where mf represents 1 to 30 and nf represents 0 to 30.) (In formula (G), mg and ng represent the average degree of polymerization, mg represents 1 to 30, and ng represents 0 to 30.) (In formula (H), mh and nh each represent an average degree of polymerization, mh represents an integer of 1 to 30, and nh represents an integer of 0 to 30.)
[0068] [ka] (In formula (I), mi and ni represent average degrees of polymerization, where mi represents 1 to 30 and ni represents 0 to 30.) (In formula (J), mj and nj represent average degrees of polymerization, mj represents 1 to 30, and nj represents 0 to 30.) (In formula (K), mk and nk represent average degrees of polymerization, mk represents 1 to 30, and nk represents 0 to 30.) (In formula (L), ml and nl represent average degrees of polymerization, ml represents 1 to 30, and nl represents 0 to 30.)
[0069] [ka] (In formula (M), mm and nm represent the average degree of polymerization, mm represents 1 to 30, and nm represents 0 to 30.) (In the formula (N), mn and nn represent average degrees of polymerization, mn represents 1 to 30, and nn represents 0 to 30.) (In formula (O), mo and no represent average degrees of polymerization, mo represents 1 to 30, and no represents 0 to 30.) (In formula (P), mp and np represent the average degree of polymerization, mp represents 1 to 30, and np represents 0 to 30.)
[0070] [ka] (In formula (Q), mq represents an average degree of polymerization, and mq represents 1 to 30.) (In formula (R), mr represents an average degree of polymerization, and mr represents 1 to 30.)
[0071] In the above formula, ma to mr may be 1 to 20, 1 to 10, or 1 to 5. na to np may be 0, 1 to 20, 1 to 10, or 1 to 5. When the compound represented by formula (1) is any of the compounds represented by the above formulas (A) to (R), the raw materials are easily available, and a lubricating layer having even better wear resistance and chemical resistance can be formed even if it is thin. This is preferable.
[0072] The number average molecular weight (Mn) of the fluorine-containing ether compound of this embodiment is preferably in the range of 500 to 10,000, more preferably in the range of 700 to 7,000, and particularly preferably in the range of 1,000 to 3,000. When the number average molecular weight is 500 or more, the lubricant containing the fluorine-containing ether compound of this embodiment is less likely to evaporate, and the lubricant can be prevented from evaporating and transferring to the magnetic head. When the number average molecular weight is 10,000 or less, the viscosity of the fluorine-containing ether compound is appropriate, and a thin lubricating layer can be easily formed by applying a lubricant containing the compound. When the number average molecular weight is 3,000 or less, the viscosity becomes easy to handle when applied to a lubricant, so it is more preferable.
[0073] The number average molecular weight (Mn) of fluorine-containing ether compounds was measured using AVANCEIII400 manufactured by Bruker Biospin. 1 H-NMR and 19 This is a value measured by F-NMR. In the NMR (nuclear magnetic resonance) measurement, the sample was diluted in a single or mixed solvent such as hexafluorobenzene, d-acetone, or d-tetrahydrofuran and used for the measurement. 19 The F-NMR chemical shift standard is the hexafluorobenzene peak at -164.7 ppm. 1 The reference for H-NMR chemical shifts was set to the acetone peak at 2.2 ppm.
[0074] "Manufacturing method" The method for producing the fluorine-containing ether compound of the present embodiment is not particularly limited, and the compound can be produced by a conventionally known production method. The fluorine-containing ether compound of the present embodiment can be produced, for example, by the production method shown below.
[0075] First, R in Equation (1)3 A fluorine-based compound is prepared in which a hydroxymethyl group (-CH2OH) is arranged at each end of a perfluoropolyether chain corresponding to the above. Next, the hydroxyl group of the hydroxymethyl group located at one end of the fluorine-based compound is converted to -R 4 (first reaction). Then, the hydroxyl group of the hydroxymethyl group located at the other end is replaced with a group consisting of R 1 -R 2 - is replaced with a group consisting of (second reaction).
[0076] The first and second reactions can be carried out by a conventional method. 1 , R 2 , R 4 The reaction time can be appropriately determined depending on the type of the catalyst, etc. In addition, either the first reaction or the second reaction may be carried out first. By the above method, the compound represented by formula (1) can be obtained.
[0077] In this embodiment, for example, R 4 When producing a fluorine-containing ether compound represented by any one of formulas (7) to (10), it is preferable to react a hydroxyl group of a hydroxymethyl group at one terminal of the fluorine-based compound with an epoxy compound corresponding to any one of formulas (7) to (10) in the first reaction. In the second reaction, the fluorine-based compound is added with R 1 -R 2 To introduce a group consisting of -, the hydroxyl group of the hydroxymethyl group at one end of the fluorine-based compound and R 1 -R 2 It is preferable to react the aryl group with an epoxy compound corresponding to the aryl group.
[0078] The epoxy compound used in producing the fluorinated ether compound of the present embodiment is, for example, R 1 -R 2 - or -R 4The epoxy compound can be synthesized by reacting an alcohol having a structure corresponding to the terminal group represented by the formula (1) with a compound having an epoxy group selected from epichlorohydrin, epibromohydrin, 2-bromoethyloxirane, and allyl glycidyl ether. Such an epoxy compound may be synthesized by a method of oxidizing an unsaturated bond, or a commercially available product may be purchased and used.
[0079] The fluorine-containing ether compound of the present embodiment is a compound represented by formula (1), R 3 and a PFPE chain represented by R 3 A methylene group (-CH2-) and a linking group (R 2 ) and a group represented by formula (2) (R 1 ) and R 3 R bonded to the second end of 4 In the lubricating layer formed on the protective layer using the lubricant containing the fluorine-containing ether compound of this embodiment, the PFPE chain and the terminal group represented by R 1 -R 2 - and -R 4 The lubricating layer containing the fluorine-containing ether compound of the present embodiment can be made thinner, which contributes to reducing the magnetic spacing in the magnetic recording medium.
[0080] Specifically, by forming a lubricating layer on a protective layer using a lubricant containing the fluorine-containing ether compound of this embodiment, <1> ~ <4> The effect is obtained. <1> R 1 is a group represented by formula (2), and R 1 Tertiary amines (R 5 R 6 Since N-) has an appropriate steric hindrance, a lubricating layer containing the fluorine-containing ether compound represented by formula (1) can obtain excellent wear resistance. <2> R 1Since the tertiary amine contained in has an appropriate mobility, the nitrogen atom in the tertiary amine can be appropriately adsorbed to the protective layer in the lubricating layer containing the fluorine-containing ether compound represented by formula (1). As a result, excellent chemical resistance is obtained.
[0081] <3> R 1 The nitrogen atom of the tertiary amine contained in R 2 A divalent linking group having an ether bond between the a As a result, the fluorine-containing ether compound represented by formula (1) has a nitrogen atom in the tertiary amine and R 2 The distance between the hydroxyl groups (-OH) in the lubricant is appropriate, and the lubricant is not likely to aggregate intramolecularly. As a result, the lubricant containing the fluorine-containing ether compound of this embodiment can cover the surface of the protective layer with a high coverage rate, and can form a lubricant layer that has good adhesion to the protective layer and excellent chemical resistance and abrasion resistance. In addition, this lubricant layer prevents the fluorine-containing ether compound from aggregating and adhering to the magnetic head as foreign matter (smear), and suppresses pick-up.
[0082] <4> R in the lubricant layer 3 The surface of the protective layer is covered by the PFPE chain represented by R, thereby reducing the friction between the magnetic head and the protective layer. 3 R linked to the first end of the PFPE chain represented by 2 and a bond between the hydroxyl group and the protective layer, and R 4 The lubricating layer is adhered to the protective layer by the bond between the polar group and the protective layer. That is, the fluorine-containing ether compound represented by formula (1) has three or more polar groups, including one or more hydroxyl groups, in the molecule, at appropriate positions, so that the interaction between the polar group and the protective layer is effectively obtained, and the surface of the protective layer is covered with a high coverage. Therefore, the lubricating layer containing the fluorine-containing ether compound of this embodiment is firmly bonded to the protective layer, and has excellent wear resistance and chemical resistance.
[0083] [Lubricants for magnetic recording media] The lubricant for a magnetic recording medium of this embodiment contains a fluorine-containing ether compound represented by formula (1). The lubricant of the present embodiment can be used by mixing, as necessary, known materials used as lubricant materials, so long as the properties resulting from the inclusion of the fluorinated ether compound represented by formula (1) are not impaired.
[0084] Specific examples of known materials include FOMBLIN (registered trademark) ZDIAC, FOMBLIN ZDEAL, FOMBLIN AM-2001 (all manufactured by Solvay Solexis), Moresco A20H (manufactured by Moresco), etc. The known material to be mixed with the lubricant of the present embodiment preferably has a number average molecular weight of 1,000 to 10,000.
[0085] When the lubricant of this embodiment contains other materials than the fluorine-containing ether compound represented by formula (1), the content of the fluorine-containing ether compound represented by formula (1) in the lubricant of this embodiment is preferably 50% by mass or more, more preferably 70% by mass or more. The content of the fluorine-containing ether compound represented by formula (1) may be 80% by mass or more, or 90% by mass or more. The upper limit can be selected arbitrarily, and may be, for example, 99% by mass or less, 95% by mass or less, or 90% by mass or less.
[0086] The lubricant of the present embodiment contains a fluorine-containing ether compound represented by formula (1), so that even if the thickness is thin, the surface of the protective layer can be covered with a high coverage rate, and a lubricant layer having excellent adhesion to the protective layer can be formed. Therefore, according to the lubricant of the present embodiment, even if the thickness is thin, a lubricant layer having excellent chemical resistance and wear resistance can be obtained.
[0087] [Magnetic recording media] The magnetic recording medium of this embodiment has at least a magnetic layer, a protective layer, and a lubricating layer provided in this order on a substrate. In the magnetic recording medium of this embodiment, one or more underlayers may be provided between the substrate and the magnetic layer, if necessary. Also, an adhesive layer and / or a soft magnetic layer may be provided between the underlayer and the substrate.
[0088] FIG. 1 is a schematic cross-sectional view showing one embodiment of a magnetic recording medium of the present invention. The magnetic recording medium 10 of this embodiment has a structure in which an adhesive layer 12, a soft magnetic layer 13, a first underlayer 14, a second underlayer 15, a magnetic layer 16, a protective layer 17, and a lubricating layer 18 are sequentially provided on a substrate 11.
[0089] "substrate" The substrate 11 may be, for example, a non-magnetic substrate in which a film made of NiP or a NiP alloy is formed on a base made of a metal or alloy material such as Al or an Al alloy. Furthermore, the substrate 11 may be a non-magnetic substrate made of a non-metallic material such as glass, ceramics, silicon, silicon carbide, carbon, or resin, or a non-magnetic substrate having a NiP or NiP alloy film formed on a base made of these non-metallic materials.
[0090] "Adhesion layer" The adhesive layer 12 prevents the progress of corrosion of the substrate 11, which occurs when the substrate 11 and the soft magnetic layer 13 provided on the adhesive layer 12 are disposed in contact with each other. The material of the adhesive layer 12 can be appropriately selected from, for example, Cr, a Cr alloy, Ti, a Ti alloy, CrTi, NiAl, an AlRu alloy, etc. The adhesive layer 12 can be formed by, for example, a sputtering method.
[0091] "Soft magnetic layer" The soft magnetic layer 13 preferably has a structure in which a first soft magnetic film, an intermediate layer made of a Ru film, and a second soft magnetic film are laminated in this order. That is, the soft magnetic layer 13 preferably has a structure in which the intermediate layer made of a Ru film is sandwiched between two soft magnetic films, and the soft magnetic films above and below the intermediate layer are anti-ferro-coupling (AFC).
[0092] Examples of materials for the first soft magnetic film and the second soft magnetic film include a CoZrTa alloy and a CoFe alloy. It is preferable to add any one of Zr, Ta, and Nb to the CoFe alloy used in the first and second soft magnetic films, which promotes the amorphization of the first and second soft magnetic films, improves the orientation of the first underlayer (seed layer), and reduces the flying height of the magnetic head. The soft magnetic layer 13 can be formed by, for example, a sputtering method.
[0093] "First base layer" The first underlayer 14 is a layer for controlling the orientation and crystal size of the second underlayer 15 and the magnetic layer 16 provided thereon. Examples of the first underlayer 14 include a Cr layer, a Ta layer, a Ru layer, or a CrMo alloy layer, a CoW alloy layer, a CrW alloy layer, a CrV alloy layer, and a CrTi alloy layer. The first underlayer 14 can be formed by, for example, a sputtering method.
[0094] "Second base layer" The second underlayer 15 is a layer that controls good orientation of the magnetic layer 16. The second underlayer 15 is preferably a layer made of Ru or a Ru alloy. The second underlayer 15 may be a layer consisting of one layer, or may be composed of multiple layers. When the second underlayer 15 is composed of multiple layers, all the layers may be composed of the same material, or at least one layer may be composed of a different material. The second underlayer 15 can be formed by, for example, a sputtering method.
[0095] "Magnetic layer" The magnetic layer 16 is a magnetic film with an easy axis of magnetization oriented perpendicular or parallel to the substrate surface. The magnetic layer 16 is, for example, a layer containing Co and Pt, and may be a layer containing an oxide, Cr, B, Cu, Ta, Zr, or the like to further improve the SNR characteristics. Examples of oxides contained in the magnetic layer 16 include SiO2, SiO, Cr2O3, CoO, Ta2O3, and TiO2.
[0096] The magnetic layer 16 may be composed of a single layer, or may be composed of multiple magnetic layers made of materials with different compositions. For example, when the magnetic layer 16 is composed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, stacked in order from the bottom, the first magnetic layer preferably has a granular structure made of a material containing Co, Cr, and Pt and further containing an oxide. As the oxide contained in the first magnetic layer, for example, oxides such as Cr, Si, Ta, Al, Ti, Mg, and Co are preferably used. Among them, TiO2, Cr2O3, SiO2, and the like can be particularly preferably used. In addition, the first magnetic layer is preferably made of a composite oxide to which two or more kinds of oxides are added. Among them, Cr2O3-SiO2, Cr2O3-TiO2, SiO2-TiO2, and the like can be particularly preferably used.
[0097] The first magnetic layer preferably contains one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, and Re, in addition to Co, Cr, Pt, and oxides. The second magnetic layer may be made of the same material as the first magnetic layer. The second magnetic layer preferably has a granular structure.
[0098] The third magnetic layer preferably has a non-granular structure made of a material that contains Co, Cr, and Pt and does not contain oxides. In addition to Co, Cr, and Pt, the third magnetic layer preferably contains one or more elements selected from B, Ta, Mo, Cu, Nd, W, Nb, Sm, Tb, Ru, Re, and Mn.
[0099] When the magnetic layer 16 is formed of multiple magnetic layers, it is preferable to provide a nonmagnetic layer between adjacent magnetic layers. When the magnetic layer 16 is formed of three layers, a first magnetic layer, a second magnetic layer, and a third magnetic layer, it is preferable to provide a nonmagnetic layer between the first magnetic layer and the second magnetic layer and between the second magnetic layer and the third magnetic layer.
[0100] The non-magnetic layer provided between adjacent magnetic layers in the magnetic layer 16 can suitably be made of, for example, Ru, a Ru alloy, a CoCr alloy, or a CoCrX1 alloy (X1 represents one or more elements selected from Pt, Ta, Zr, Re, Ru, Cu, Nb, Ni, Mn, Ge, Si, O, N, W, Mo, Ti, V, and B).
[0101] For the non-magnetic layer provided between adjacent magnetic layers of the magnetic layer 16, it is preferable to use an alloy material containing an oxide, a metal nitride, or a metal carbide. Specifically, for example, SiO2, Al2O3, Ta2O5, Cr2O3, MgO, Y2O3, TiO2, etc. can be preferably used as the oxide. For example, AlN, Si3N4, TaN, CrN, etc. can be preferably used as the metal nitride. For example, TaC, BC, SiC, etc. can be preferably used as the metal carbide. The nonmagnetic layer can be formed by, for example, a sputtering method.
[0102] In order to achieve higher recording density, the magnetic layer 16 is preferably a magnetic layer for perpendicular magnetic recording in which the axis of easy magnetization is oriented perpendicular to the substrate surface, but may also be a magnetic layer for in-plane magnetic recording. The magnetic layer 16 may be formed by any known method such as vapor deposition, ion beam sputtering, magnetron sputtering, etc. The magnetic layer 16 is usually formed by sputtering.
[0103] "Protective layer" The protective layer 17 protects the magnetic layer 16. The protective layer 17 may be made of a single layer or multiple layers. Examples of materials for the protective layer 17 include carbon, carbon containing nitrogen, and silicon carbide. A carbon-based protective layer, particularly an amorphous carbon protective layer, can be preferably used as the protective layer 17. When the protective layer 17 is a carbon-based protective layer, the interaction with the hydroxyl group contained in the fluorine-containing ether compound in the lubricating layer 18 is further enhanced, which is preferable.
[0104] The adhesion between the carbon-based protective layer and the lubricating layer 18 can be controlled by making the carbon-based protective layer from hydrogenated carbon and / or nitrogenated carbon and adjusting the hydrogen content and / or nitrogen content in the carbon-based protective layer. The hydrogen content in the carbon-based protective layer is preferably 3 to 20 atomic % when measured by hydrogen forward scattering (HFS). The nitrogen content in the carbon-based protective layer is preferably 4 to 15 atomic % when measured by X-ray photoelectron spectroscopy (XPS).
[0105] The hydrogen and / or nitrogen contained in the carbon-based protective layer does not need to be uniformly contained throughout the carbon-based protective layer. The carbon-based protective layer is preferably a compositionally graded layer in which, for example, nitrogen is contained on the lubricating layer 18 side of the protective layer 17, and hydrogen is contained on the magnetic layer 16 side of the protective layer 17. In this case, the adhesion between the magnetic layer 16 and the lubricating layer 18 and the carbon-based protective layer is further improved.
[0106] The thickness of the protective layer 17 can be selected arbitrarily, but is preferably 1 nm to 7 nm. If the thickness of the protective layer 17 is 1 nm or more, sufficient performance as the protective layer 17 can be obtained. If the thickness of the protective layer 17 is 7 nm or less, it is preferable from the viewpoint of making the protective layer 17 thinner.
[0107] The protective layer 17 can be formed by a sputtering method using a target material containing carbon, a CVD (chemical vapor deposition) method using a hydrocarbon raw material such as ethylene or toluene, an IBD (ion beam deposition) method, or the like. When a carbon-based protective layer is formed as the protective layer 17, it can be deposited by, for example, a DC magnetron sputtering method. In particular, when a carbon-based protective layer is formed as the protective layer 17, it is preferable to deposit an amorphous carbon protective layer by a plasma CVD method. The amorphous carbon protective layer deposited by the plasma CVD method has a uniform surface with small roughness.
[0108] "Lubricant layer" The lubricating layer 18 prevents contamination of the magnetic recording medium 10. In addition, the lubricating layer 18 reduces the frictional force of the magnetic head of the magnetic recording and reproducing device that slides on the magnetic recording medium 10, thereby improving the durability of the magnetic recording medium 10. 1, the lubricating layer 18 is formed on and in contact with the protective layer 17. The lubricating layer 18 contains the above-mentioned fluorine-containing ether compound.
[0109] When the protective layer 17 disposed below the lubricating layer 18 is a carbon-based protective layer, the lubricating layer 18 is bonded with a high bonding strength to the protective layer 17. As a result, even if the thickness of the lubricating layer 18 is thin, it is easy to obtain a magnetic recording medium 10 in which the surface of the protective layer 17 is covered with a high coverage rate, and contamination of the surface of the magnetic recording medium 10 can be effectively prevented.
[0110] The average thickness of the lubricating layer 18 can be selected arbitrarily, but is preferably 0.5 nm (5 Å) to 2 nm (20 Å), and more preferably 0.5 nm (5 Å) to 1 nm (10 Å). When the average thickness of the lubricating layer 18 is 0.5 nm or more, the lubricating layer 18 is formed with a uniform thickness without being island-shaped or mesh-shaped. Therefore, the surface of the protective layer 17 can be covered with the lubricating layer 18 with a high coverage rate. In addition, by setting the average thickness of the lubricating layer 18 to 2 nm or less, the lubricating layer 18 can be made sufficiently thin, and the flying height of the magnetic head can be sufficiently reduced.
[0111] If the surface of the protective layer 17 is not covered with the lubricating layer 18 at a sufficiently high coverage rate, environmental substances adsorbed to the surface of the magnetic recording medium 10 will pass through the gaps in the lubricating layer 18 and penetrate underneath the lubricating layer 18. The environmental substances that penetrate underneath the lubricating layer 18 will be adsorbed and bonded to the protective layer 17 to generate contaminants. Then, during magnetic recording and reproduction, these contaminants (aggregated components) will adhere (transfer) to the magnetic head as smear, damaging the magnetic head or degrading the magnetic recording and reproduction characteristics of the magnetic recording and reproduction device.
[0112] Examples of environmental substances that generate pollutants include siloxane compounds (cyclic siloxanes, linear siloxanes), ionic impurities, hydrocarbons with relatively high molecular weights such as octacosane, and plasticizers such as dioctyl phthalate. Examples of metal ions contained in ionic impurities include sodium ions and potassium ions. Examples of inorganic ions contained in ionic impurities include chloride ions, bromide ions, nitrate ions, sulfate ions, and ammonium ions. Examples of organic ions contained in ionic impurities include oxalate ions and formate ions.
[0113] "Method of forming lubricating layer" The method for forming the lubricating layer 18 can be selected arbitrarily, but one example is a method in which a magnetic recording medium in the middle of manufacture is prepared in which each layer up to the protective layer 17 is formed on the substrate 11, and a solution for forming a lubricating layer is applied onto the protective layer 17 and dried.
[0114] The lubricant layer forming solution can be obtained, for example, by dispersing and dissolving the lubricant for magnetic recording media of the above-mentioned embodiment in a solvent as necessary, and adjusting the viscosity and concentration to be suitable for the coating method. Examples of the solvent used in the lubricant layer forming solution include fluorine-based solvents such as Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals).
[0115] The method for applying the solution for forming the lubricating layer is not particularly limited, but examples thereof include spin coating, spraying, paper coating, and dipping. When using the dipping method, for example, the following method can be used. First, the substrate 11 on which each layer up to the protective layer 17 has been formed is immersed in the lubricant layer forming solution placed in the immersion tank of a dip coater. Next, the substrate 11 is lifted from the immersion tank at a predetermined speed. In this way, the lubricant layer forming solution is applied to the surface of the substrate 11 above the protective layer 17. By using the dipping method, the lubricant layer forming solution can be applied uniformly onto the surface of the protective layer 17, and the lubricant layer 18 can be formed on the protective layer 17 with a uniform thickness.
[0116] In this embodiment, it is preferable to perform a heat treatment on the substrate 11 on which the lubricating layer 18 is formed. By performing the heat treatment, the adhesion between the lubricating layer 18 and the protective layer 17 is improved, and the adhesive force between the lubricating layer 18 and the protective layer 17 is improved. The heat treatment temperature can be selected arbitrarily, but is preferably 100 to 180° C. If the heat treatment temperature is 100° C. or higher, the effect of improving the adhesion between the lubricating layer 18 and the protective layer 17 can be sufficiently obtained. Furthermore, by setting the heat treatment temperature to 180° C. or lower, thermal decomposition of the lubricating layer 18 can be prevented. The heat treatment time is preferably 10 to 120 minutes.
[0117] The magnetic recording medium 10 of this embodiment is a medium in which at least a magnetic layer 16, a protective layer 17, and a lubricating layer 18 are sequentially provided on a substrate 11. In the magnetic recording medium 10 of this embodiment, a lubricating layer 18 containing the above-mentioned fluorine-containing ether compound is formed on the protective layer 17. Even though the lubricating layer 18 is thin, it covers the surface of the protective layer 17 with a high coverage rate. Therefore, in the magnetic recording medium 10 of this embodiment, environmental substances that generate contaminants such as ionic impurities are prevented from penetrating through the gaps in the lubricating layer 18. Therefore, the magnetic recording medium 10 of this embodiment has a small amount of contaminants present on its surface. In addition, the lubricating layer 18 in the magnetic recording medium 10 of this embodiment is less likely to generate foreign matter (smear), and can suppress pickup. In addition, the lubricating layer 18 in the magnetic recording medium 10 of this embodiment has excellent chemical resistance and wear resistance. Therefore, the magnetic recording medium 10 of this embodiment has excellent reliability and durability. EXAMPLES
[0118] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0119] [Example 1] The compound represented by the above formula (A) was obtained by the method described below. In a nitrogen gas atmosphere, HOCH2CF2O (CF2CF2O) was added to a 100 mL eggplant flask. m (CF2O) n 40 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (where m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5), 4.9 g of a compound represented by the following formula (11) (molecular weight 202.3, 24 mmol) and 38 mL of t-butanol were charged and stirred at room temperature until homogenized to obtain a mixture. 1.4 g of potassium tert-butoxide (molecular weight 112.21, 12 mmol) was added to this mixture and reacted by stirring at 70°C for 16 hours.
[0120] The compound represented by formula (11) used in the reaction was synthesized by oxidizing a compound in which ethylene glycol monoallyl ether was protected with dihydropyran.
[0121] The reaction product obtained after the reaction was cooled to 25°C, transferred to a separatory funnel containing 100mL of water, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 19.2g (molecular weight 1202.3, 15.9mmol) of a compound represented by the following formula (12) as an intermediate.
[0122] [ka] (In formula (12), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0123] Next, in a nitrogen gas atmosphere, 5.95 g (molecular weight 1202.3, 5.0 mmol) of the compound represented by formula (12), which is the intermediate obtained above, 0.942 g (molecular weight 171.24, 5.5 mmol) of the compound represented by the following formula (13), and 2.4 mL of t-butanol were charged into a 100 mL eggplant flask and stirred at room temperature until homogenized. 1.87 g (molecular weight 112.21, 25.2 mmol) of potassium tert-butoxide was added to this homogenous liquid and reacted by stirring at 70°C for 22.5 hours.
[0124] [ka]
[0125] The compound represented by formula (13) used in the reaction was synthesized by reacting the primary hydroxyl group of 1-(2-hydroxyethyl)pyrrolidine with epibromohydrin.
[0126] The reaction solution obtained after the reaction was returned to room temperature, 26 g of 10% hydrogen chloride-methanol solution (product name: X0041, hydrogen chloride-methanol reagent (5-10%), manufactured by Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at room temperature for 3.5 hours. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 4.25 g (molecular weight 1289, 3.3 mmol) of compound (A) (in formula (A), ma, which indicates the average degree of polymerization, is 4.5, and na, which indicates the average degree of polymerization, is 4.5).
[0127] The obtained compound (A) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (A); 1 H-NMR(CD3COCD3);δ[ppm]=1.78~1.82(4H), 2.50~2.65(6H), 3.42~4.50(23H)
[0128] Example 2 The same operation as in Example 1 was carried out except that 1.02 g of a compound represented by the following formula (14) was used instead of the compound represented by formula (13), thereby obtaining 4.30 g of a compound represented by the above formula (B) (in formula (B), mb indicating the average degree of polymerization is 4.5, and nb indicating the average degree of polymerization is 4.5). The compound represented by formula (14) used in the reaction was synthesized by reacting the primary hydroxyl group of 1-piperidineethanol with epibromohydrin.
[0129] [ka]
[0130] The obtained compound (B) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (B); 1 H-NMR(CD3COCD3);δ[ppm]=1.46~1.59(6H), 2.53~2.79(6H), 3.41~4.49(23H)
[0131] Example 3 The same procedure as in Example 1 was carried out, except that 1.03 g of a compound represented by the following formula (15) was used instead of the compound represented by formula (13), to obtain 4.31 g of a compound represented by the above formula (C) (in formula (C), mc, which indicates the average degree of polymerization, is 4.5, and nc, which indicates the average degree of polymerization, is 4.5). The compound represented by formula (15) used in the reaction was synthesized by reacting the primary hydroxyl group of 4-(2-hydroxyethyl)morpholine with epibromohydrin.
[0132] [ka]
[0133] The obtained compound (C) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (C); 1 H-NMR(CD3COCD3);δ[ppm]=2.43~2.54(6H), 3.40~4.68(27H)
[0134] Example 4 The same procedure as in Example 1 was carried out, except that 1.10 g of a compound represented by the following formula (16) was used instead of the compound represented by formula (13), to obtain 4.35 g of a compound represented by the above formula (D) (in formula (D), md indicating the average degree of polymerization is 4.5, and nd indicating the average degree of polymerization is 4.5). The compound represented by formula (16) used in the reaction was synthesized by reacting the primary hydroxyl group of hexahydro-1H-azepine-1-ethanol with epibromohydrin.
[0135] [ka]
[0136] The obtained compound (D) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (D); 1 H-NMR(CD3COCD3);δ[ppm]=1.60~1.69(8H), 2.50~2.82(6H), 3.43~4.62(23H)
[0137] Example 5 The compound represented by the above formula (E) was produced by the method shown below. In a nitrogen gas atmosphere, HOCH2CF2O (CF2CF2O) was added to a 100 mL eggplant flask. m (CF2O) n40g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (in the formula, m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5), 7.69g of a compound represented by the following formula (17) (molecular weight 320.38, 24mmol), and 38mL of t-butanol were charged and stirred at room temperature until homogenized. 1.4g of potassium tert-butoxide (molecular weight 112.21, 12mmol) was further added to this homogenous liquid, and the mixture was reacted by stirring at 70°C for 16 hours.
[0138] The compound represented by formula (17) used in the reaction was synthesized using the method shown below. A tert-butyldimethylsilyl (TBS) group was introduced as a protecting group to the primary hydroxyl group of 3-allyloxy-1,2-propanediol, and a methoxymethyl (MOM) group was introduced as a protecting group to the secondary hydroxyl group of the obtained compound. The TBS group was then removed from the compound, and the resulting primary hydroxyl group was reacted with 2-bromoethoxytetrahydropyran. The double bond of the obtained compound was oxidized. The compound represented by formula (17) was obtained by the above steps.
[0139] The reaction product obtained after the reaction was cooled to 25°C, transferred to a separatory funnel containing 100mL of water, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 21.00g (molecular weight 1320.38, 15.9mmol) of a compound represented by the following formula (18) as an intermediate.
[0140] [ka] (In formula (18), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0141] Next, in a nitrogen gas atmosphere, 6.60 g (molecular weight 1320.38, 5.0 mmol) of the compound represented by formula (18), which is the intermediate obtained above, 0.942 g (molecular weight 171.24, 5.5 mmol) of the compound represented by formula (13) above, and 2.4 mL of t-butanol were charged into a 100 mL eggplant flask, and stirred at room temperature until homogenized. 1.87 g (molecular weight 112.21, 25.2 mmol) of potassium tert-butoxide was added to this homogenous liquid, and the mixture was reacted by stirring at 70°C for 22.5 hours.
[0142] The reaction solution obtained after the reaction was returned to room temperature, 26 g of 10% hydrogen chloride-methanol solution (product name: X0041, hydrogen chloride-methanol reagent (5-10%), manufactured by Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at room temperature for 3.5 hours. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 4.50 g (molecular weight 1363, 3.3 mmol) of compound (E) (in formula (E), me, which indicates the average degree of polymerization, is 4.5, and ne, which indicates the average degree of polymerization, is 4.5).
[0143] The obtained compound (E) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (E); 1 H-NMR(CD3COCD3)δ[ppm]=1.77~1.82(4H), 2.54~2.65(6H), 3.42~4.55(29H)
[0144] Example 6 The same procedure as in Example 5 was carried out except that 1.02 g of the compound represented by the above formula (14) was used instead of the compound represented by the formula (13), to obtain 4.55 g of the compound represented by the above formula (F) (in formula (F), mf indicating the average degree of polymerization is 4.5, and nf indicating the average degree of polymerization is 4.5).
[0145] The obtained compound (F) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (F); 1 H-NMR(CD3COCD3);δ[ppm]=1.45~1.60(6H), 2.51~2.69(6H), 3.41~4.52(29H)
[0146] Example 7 The same procedure as in Example 5 was carried out except that 1.03 g of the compound represented by the above formula (15) was used instead of the compound represented by the formula (13), to obtain 4.55 g of the compound represented by the above formula (G) (in the formula (G), mg indicates the average degree of polymerization is 4.5, and ng indicates the average degree of polymerization is 4.5).
[0147] The obtained compound (G) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (G); 1 H-NMR(CD3COCD3);δ[ppm]=2.42~2.53(6H), 3.40~4.70(33H)
[0148] Example 8 The same procedure as in Example 5 was carried out except that 1.03 g of the compound represented by the above formula (16) was used instead of the compound represented by the formula (13), to obtain 4.55 g of the compound represented by the above formula (H) (in formula (H), mh indicating the average degree of polymerization is 4.5, and nh indicating the average degree of polymerization is 4.5).
[0149] The obtained compound (H) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (H); 1 H-NMR(CD3COCD3);δ[ppm]=1.56~1.68(8H), 2.44~2.77(6H), 3.42~4.71(29H)
[0150] Example 9 The same procedure as in Example 5 was carried out, except that 1.81 g of a compound represented by the following formula (19) was used instead of the compound represented by formula (13), to obtain 4.74 g of a compound represented by the above formula (I) (in formula (I), mi indicating the average degree of polymerization is 4.5, and ni indicating the average degree of polymerization is 4.5).
[0151] [ka]
[0152] The compound represented by formula (19) used in the reaction was synthesized by the method shown below. Allyl glycidyl ether was reacted with the primary hydroxyl group of 1-(2-hydroxyethyl)pyrrolidine. The secondary hydroxyl group of the obtained compound was protected with a tetrahydropyranyl (THP) group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (19) was obtained by the above steps.
[0153] The obtained compound (I) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (I); 1 H-NMR(CD3COCD3);δ[ppm]=1.76~1.82(4H), 2.50~2.63(6H), 3.42~4.65(35H)
[0154] Example 10 The same procedure as in Example 5 was carried out, except that 1.89 g of a compound represented by the following formula (20) was used instead of the compound represented by formula (13), to obtain 4.79 g of a compound represented by the above formula (J) (in formula (J), mj indicating the average degree of polymerization is 4.5, and nj indicating the average degree of polymerization is 4.5).
[0155] [ka]
[0156] The compound represented by formula (20) used in the reaction was synthesized by the method shown below. Allyl glycidyl ether was reacted with the primary hydroxyl group of 1-piperidineethanol. The secondary hydroxyl group of the obtained compound was protected with a THP group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (20) was obtained by the above steps.
[0157] The obtained compound (J) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (J); 1 H-NMR(CD3COCD3);δ[ppm]=1.45~1.59(6H), 2.57~2.78(6H), 3.42~4.54(35H)
[0158] Example 11 The same procedure as in Example 5 was carried out, except that 1.90 g of a compound represented by the following formula (21) was used instead of the compound represented by formula (13), to obtain 4.80 g of a compound represented by the above formula (K) (in formula (K), mk indicating the average degree of polymerization is 4.5, and nk indicating the average degree of polymerization is 4.5).
[0159] [ka]
[0160] The compound represented by formula (21) used in the reaction was synthesized by the method shown below. The primary hydroxyl group of 4-(2-hydroxyethyl)morpholine was reacted with allyl glycidyl ether. The secondary hydroxyl group of the obtained compound was protected with a THP group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (21) was obtained by the above steps.
[0161] The obtained compound (K) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (K); 1 H-NMR(CD3COCD3);δ[ppm]=2.47~2.55(6H), 3.46~4.76(39H)
[0162] Example 12 The same procedure as in Example 5 was carried out, except that 2.00 g of a compound represented by the following formula (22) was used instead of the compound represented by formula (13), to obtain 4.84 g of a compound represented by the above formula (L) (in formula (L), ml indicating the average degree of polymerization is 4.5, and nl indicating the average degree of polymerization is 4.5).
[0163] [ka]
[0164] The compound represented by formula (22) used in the reaction was synthesized by the method shown below. Allyl glycidyl ether was reacted with the primary hydroxyl group of hexahydro-1H-azepine-1-ethanol. The secondary hydroxyl group of the obtained compound was protected with a THP group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (22) was obtained by the above steps.
[0165] The obtained compound (L) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (L); 1 H-NMR(CD3COCD3);δ[ppm]=1.52~1.63(8H), 2.46~2.80(6H), 3.40~4.68(35H)
[0166] (Example 13) The compound represented by the above formula (M) was produced by the method shown below. In a nitrogen gas atmosphere, HOCH2CF2O (CF2CF2O) was added to a 100 mL eggplant flask. m (CF2O) n40 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (where m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5), 8.03 g of a compound represented by the following formula (23) (molecular weight 334.41, 24 mmol), and 38 mL of t-butanol were charged and stirred at room temperature until homogenized. 1.4 g of potassium tert-butoxide (molecular weight 112.21, 12 mmol) was further added to this homogenous liquid, and the mixture was reacted at 70°C for 16 hours with stirring.
[0167] The compound represented by formula (23) used in the reaction was synthesized using the method shown below. A tert-butyldimethylsilyl (TBS) group was introduced as a protecting group to the primary hydroxyl group of 3-allyloxy-1,2-propanediol, and a methoxymethyl (MOM) group was introduced as a protecting group to the secondary hydroxyl group of the obtained compound. After that, the TBS group of the obtained compound was removed, and the resulting primary hydroxyl group was reacted with 2-(chloropropoxy)tetrahydro-2H-pyran. The double bond of the obtained compound was oxidized. The compound represented by formula (23) was obtained by the above steps.
[0168] The reaction product obtained after the reaction was cooled to 25°C, transferred to a separatory funnel containing 100mL of water, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 21.27g (molecular weight 1334.41, 15.9mmol) of the compound represented by the following formula (24) as an intermediate.
[0169] [ka] (In formula (24), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0170] Next, in a nitrogen gas atmosphere, 6.67 g (molecular weight 1334.41, 5.0 mmol) of the compound represented by formula (24), which is the intermediate obtained above, 1.89 g (molecular weight 343.46, 5.5 mmol) of the compound represented by the following formula (25), and 2.4 mL of t-butanol were charged into a 100 mL eggplant flask and stirred at room temperature until homogenized. 1.87 g (molecular weight 112.21, 25.2 mmol) of potassium tert-butoxide was added to this homogenous liquid and reacted by stirring at 70°C for 22.5 hours.
[0171] [ka]
[0172] The compound represented by formula (25) used in the reaction was synthesized by the method shown below. Allyl glycidyl ether was reacted with the primary hydroxyl group of 1-(3-hydroxypropyl)pyrrolidine. The secondary hydroxyl group of the obtained compound was protected with a tetrahydropyranyl (THP) group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (25) was obtained by the above steps.
[0173] The reaction solution obtained after the reaction was returned to room temperature, 26 g of 10% hydrogen chloride-methanol solution (product name: X0041, hydrogen chloride-methanol reagent (5-10%), manufactured by Tokyo Chemical Industry Co., Ltd.) was added, and the mixture was stirred at room temperature for 3.5 hours. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 4.84 g (molecular weight 1466, 3.3 mmol) of compound (M) (in formula (M), mm, which indicates the average degree of polymerization, is 4.5, and nm, which indicates the average degree of polymerization, is 4.5).
[0174] The obtained compound (M) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (M); 1H-NMR(CD3COCD3);δ[ppm]=1.62~1.68(2H), 1.75~1.80(4H), 2.51~2.59(6H), 3.46~4.66(37H)
[0175] Example 14 The compound represented by the following formula (N) was synthesized by the following method. The same procedure as in Example 1 was carried out, except that 0.80 g of a compound represented by the following formula (26) was used instead of the compound represented by formula (13), to obtain 4.17 g of a compound represented by the above formula (N) (in formula (N), mn indicating the average degree of polymerization is 4.5, and nn indicating the average degree of polymerization is 4.5). The compound represented by formula (26) used in the reaction was synthesized by reacting epibromohydrin with the primary hydroxyl group of 2-(dimethylamino)ethanol.
[0176] [ka]
[0177] The obtained compound (N) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (N); 1 H-NMR(CD3COCD3);δ[ppm]=2.27(6H), 2.45~2.48(2H), 3.42~4.60(23H)
[0178] Example 15 The compound represented by the following formula (O) was synthesized by the following method. The same procedure as in Example 1 was carried out, except that 0.88 g of a compound represented by the following formula (27) was used instead of the compound represented by formula (13), to obtain 4.22 g of a compound represented by the above formula (O) (in formula (O), mo indicating the average degree of polymerization is 4.5, and no indicating the average degree of polymerization is 4.5). The compound represented by formula (27) used in the reaction was synthesized by reacting the primary hydroxyl group of 3-(dimethylamino)-1-propanol with epibromohydrin.
[0179] [ka]
[0180] The obtained compound (O) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (O); 1 H-NMR(CD3COCD3);δ[ppm]=1.66~1.69(2H), 2.27(6H), 2.51~2.53(2H), 3.49~4.60(23H)
[0181] Example 16 The compound represented by the following formula (P) was synthesized by the following method. The same procedure as in Example 1 was carried out, except that 1.82 g of a compound represented by the following formula (28) was used instead of the compound represented by formula (13), to obtain 4.51 g of a compound represented by the above formula (P) (in formula (P), mp indicating the average degree of polymerization is 4.5, and np indicating the average degree of polymerization is 4.5).
[0182] [ka]
[0183] The compound represented by formula (28) used in the reaction was synthesized by the method shown below. Allyl glycidyl ether was reacted with the primary hydroxyl group of 2-diethylaminoethanol. The secondary hydroxyl group of the obtained compound was protected with a tetrahydropyranyl (THP) group, and the terminal double bond of the obtained compound was oxidized. The compound represented by formula (28) was obtained by the above steps.
[0184] The obtained compound (P) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (P); 1 H-NMR(CD3COCD3);δ[ppm]=1.03(6H), 2.50~2.58(6H), 3.42~4.68(29H)
[0185] (Example 17) The compound represented by the above formula (Q) was obtained by the method described below. HOCH2CF2O(CF2CF2O) m (CF2O) n Instead of the compound represented by CF2CH2OH (where m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5), HOCH2CF2O(CF2CF2O) s The same procedure as in Example 1 was carried out except that 40 g of a compound represented by CF2CH2OH (wherein s, which indicates the average degree of polymerization, is 7.1), was used, thereby obtaining 4.25 g of a compound represented by the above formula (Q) (wherein mq, which indicates the average degree of polymerization, is 7.1).
[0186] (Example 18) The compound represented by the above formula (R) was obtained by the method described below. HOCH2CF2O(CF2CF2O) m (CF2O) n Instead of the compound represented by CF2CH2OH (where m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5), HOCH2CF2CF2(OCF2CF2CF2) t The same operation as in Example 1 was carried out except for using 40 g of a compound represented by OCF2CF2CH2OH (wherein t, which indicates the average degree of polymerization, is 4.4), to obtain 4.25 g of a compound represented by the above formula (R) (wherein mr, which indicates the average degree of polymerization, is 4.4).
[0187] Comparative Example 1 The compound represented by the following formula (S) was synthesized by the following method. The same procedure as in Example 1 was carried out, except that 0.99 g of a compound represented by the following formula (29) was used instead of the compound represented by formula (13), to obtain 4.28 g of a compound represented by the following formula (S). The compound represented by formula (29) used in the reaction was synthesized by reacting epibromohydrin with the primary hydroxyl group of pyridine-4-ethanol.
[0188] [ka] (In formula (S), ms indicating the average degree of polymerization is 4.5, and ns indicating the average degree of polymerization is 4.5.)
[0189] The obtained compound (S) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (S); 1 H-NMR(CD3COCD3);δ[ppm]=2.82~2.85(2H), 3.39~4.66(23H), 7.39~8.63(4H)
[0190] Comparative Example 2 The compound represented by the following formula (T) was synthesized by the following method. In a nitrogen gas atmosphere, 5.95 g (molecular weight 1202.3, 5.0 mmol) of the compound represented by formula (12), which is the intermediate produced in Example 1, 0.40 g (molecular weight 24.0, 10.0 mmol) of 60% sodium hydride, and 2.4 mL of N,N-dimethylformamide were charged into a 100 mL eggplant flask, and stirred at room temperature until homogenized. 0.59 g (molecular weight 107.58, 5.5 mmol) of N,N-dimethyl-2-chloroethylamine was added to this homogenous liquid, and the mixture was reacted by stirring at 70°C for 22.5 hours.
[0191] The reaction solution obtained after the reaction was returned to room temperature, water was added, and the mixture was stirred at room temperature for 10 minutes. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate water, and 100 mL of saline, in that order, and dehydrated with anhydrous sodium sulfate. The drying agent was filtered off, and the filtrate was concentrated.
[0192] To the concentrated filtrate, 26 g of 10% hydrogen chloride-methanol solution (product name: X0041, hydrogen chloride-methanol reagent (5-10%), manufactured by Tokyo Chemical Industry Co., Ltd.) was added and stirred at room temperature for 3.5 hours. The reaction solution was transferred little by little to a separatory funnel containing 100 mL of saline, and extracted twice with 200 mL of ethyl acetate. The organic layer was washed with 100 mL of saline, 100 mL of saturated sodium bicarbonate solution, and 100 mL of saline, in that order, and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 3.98 g of compound (T) (molecular weight 1205, 3.3 mmol).
[0193] [ka] (In formula (T), mt, which indicates the average degree of polymerization, is 4.5, and nt, which indicates the average degree of polymerization, is 4.5.)
[0194] The obtained compound (T) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (T); 1 H-NMR(CD3COCD3);δ[ppm]=2.26(6H), 2.43~2.46(2H), 3.45~4.64(17H)
[0195] Comparative Example 3 The compound represented by the following formula (U) was synthesized by the method described in the examples of Patent Document 1. HOCH2CF2O(CF2CF2O) m (CF2O) n From 4.20 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (where m, indicating the average degree of polymerization, is 4.5, and n, indicating the average degree of polymerization, is 4.5), using the method described in the examples of JP-A-62-57418, 4.12 g of a compound represented by the following formula (30) having a glycidyl group at the molecular end was obtained.
[0196] Next, 40 mL of dimethylamine aqueous solution (50%) was added to the compound represented by formula (30), and the mixture was stirred at room temperature for 4 hours to react. After the reaction, the oil layer was separated from the reaction product obtained, dissolved in 100 mL of Vertrel (registered trademark) XF, and dehydrated with anhydrous sodium sulfate. After filtering the desiccant, the filtrate was concentrated to synthesize 3.97 g (molecular weight 1202, 3.3 mmol) of compound (U).
[0197] [ka] (In formula (30), m, which indicates the average degree of polymerization, is 4.5, and n, which indicates the average degree of polymerization, is 4.5.) (In formula (U), mu indicating the average degree of polymerization is 4.5, and nu indicating the average degree of polymerization is 4.5.)
[0198] The obtained compound (U) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (U); 1 H-NMR(CDCl3);δ[ppm]=2.11~2.19(1H), 2.32(6H), 2.37~2.50(1H), 3.51~3.74(2H), 3.78~4.03(4H)
[0199] Comparative Example 4 The compound represented by the following formula (V) was synthesized by the following method. 2.5 g of trifluoromethanesulfonic acid chloride and 0.92 g of dimethylaminopyridine were added and stirred at -20°C. Then, HOCH2CF2O(CF2CF2O) m (CF2O) n 5.0 g of a compound (number average molecular weight 1000, molecular weight distribution 1.1) represented by CF2CH2OH (where m indicating the average degree of polymerization is 4.5, and n indicating the average degree of polymerization is 4.5) was added dropwise and reacted for 2 hours.
[0200] After the reaction, the reaction product was returned to room temperature, transferred to a separatory funnel containing 100 mL of water, and extracted three times with 100 mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 6.4 g (molecular weight 1264, 5.1 mmol) of the compound represented by the following formula (31) as an intermediate.
[0201] [ka] (In formula (31), m representing the average degree of polymerization is 4.5, and n representing the average degree of polymerization is 4.5.)
[0202] Under a nitrogen gas atmosphere, 6.0 g (molecular weight 1264.1, 4.8 mmol) of the compound represented by formula (31), which is the intermediate obtained above, 1.3 g (molecular weight 89.14, 14.2 mmol) of 2-(ethylamino)ethanol, and 12.4 mL of acetonitrile were placed in a 100 mL recovery flask and stirred at room temperature until the mixture became homogeneous, and then heated under reflux and stirred for 6 hours.
[0203] After the reaction, the reaction product was cooled to 25°C, transferred to a separatory funnel containing 100mL of saturated sodium bicarbonate solution, and extracted three times with 100mL of ethyl acetate. The organic layer was washed with water and dehydrated with anhydrous sodium sulfate. After filtering off the desiccant, the filtrate was concentrated, and the residue was purified by silica gel column chromatography to obtain 3.78g (molecular weight 1144, 3.3mmol) of compound (V) (in formula (V), mv indicating the average degree of polymerization is 4.5, and nv indicating the average degree of polymerization is 4.5).
[0204] [ka] (In formula (V), mv indicating the average degree of polymerization is 4.5, and nv indicating the average degree of polymerization is 4.5.)
[0205] The obtained compound (V) 1H-NMR measurement was performed, and the structure was identified from the following results. Compound (V); 1 H-NMR(CD3COCD3);δ[ppm]=1.05(6H), 2.58~2.67(8H), 3.37~3.68(10H)
[0206] Comparative Example 5 The compound represented by the following formula (W) was synthesized by the following method. The same operation as in Example 1 was carried out, except that 3.80 g of a compound represented by the following formula (32) was used instead of the compound represented by formula (11), and 0.80 g of a compound represented by the above formula (26) was used instead of the compound represented by formula (13), to obtain 4.02 g of a compound represented by the following formula (W). The compound represented by formula (32) used in the reaction was synthesized by protecting the primary hydroxyl group of 2,3-epoxy-1-propanol with dihydropyran.
[0207] [ka]
[0208] [ka] (In formula (W), mw indicating the average degree of polymerization is 4.5, and nw indicating the average degree of polymerization is 4.5.)
[0209] The obtained compound (W) 1 H-NMR measurement was performed, and the structure was identified from the following results. Compound (W); 1 H-NMR(CD3COCD3);δ[ppm]=2.25(6H), 2.46~2.48(2H), 3.41~4.54(19H)
[0210] The compounds of Examples 1 to 18 and Comparative Examples 1 to 5 thus obtained are represented by the formula (1) 1 The structure of (R in formula (2) 5 R 6N-, and a), R 2 (b in formula (3)), R 3 The structure of R 4 The structures are shown in Tables 1 to 3. For Comparative Examples 1 to 5, R 1 In the column of the structure (R in formula (2) 5 R 6 N-), when the compounds of Comparative Examples 1 to 5 are applied to formula (1), R 5 R 6 The terminal group placed at the N-position is described.
[0211] The number average molecular weights (Mn) of the compounds of Examples 1 to 18 and Comparative Examples 1 to 5 were calculated using the above-mentioned 1 H-NMR and 19 The average molecular weights were determined by F-NMR measurement. The results are shown in Tables 1 to 3. It is estimated that the average molecular weights of the synthesized compounds vary by about 1 to 5 due to the molecular weight distribution of the fluoropolyether used as the raw material of the compounds, differences in the operations used to synthesize the compounds, and the like.
[0212] [Table 1]
[0213] [Table 2]
[0214] [Table 3]
[0215] Next, a solution for forming a lubricant layer was prepared by the method described below using the compounds obtained in Examples 1 to 18 and Comparative Examples 1 to 5. Then, using the obtained solution for forming a lubricant layer, a lubricant layer for a magnetic recording medium was formed by the method described below, and the magnetic recording media of Examples 1 to 18 and Comparative Examples 1 to 5 were obtained.
[0216] "Lubricant layer forming solution" The compounds obtained in Examples 1 to 18 and Comparative Examples 1 to 5 were each dissolved in a fluorine-based solvent, Vertrel (registered trademark) XF (product name, manufactured by Mitsui DuPont Fluorochemicals Co., Ltd.), and diluted with Vertrel XF so that the film thickness when applied onto the protective layer would be 9 Å to 10 Å, to prepare a solution for forming a lubricating layer.
[0217] "Magnetic recording media" A magnetic recording medium was prepared by sequentially providing an adhesive layer, a soft magnetic layer, a first underlayer, a second underlayer, a magnetic layer, and a protective layer on a substrate having a diameter of 65 mm. The protective layer was made of carbon. On the protective layer of the magnetic recording medium on which each layer up to the protective layer had been formed, the lubricant layer forming solutions of Examples 1 to 18 and Comparative Examples 1 to 5 were applied by dipping. The dipping was performed under the conditions of an immersion speed of 10 mm / sec, an immersion time of 30 sec, and a pull-up speed of 1.2 mm / sec.
[0218] The magnetic recording medium coated with the lubricant layer-forming solution was then placed in a thermostatic chamber at 120°C and heated for 10 minutes to remove the solvent in the lubricant layer-forming solution, thereby forming a lubricant layer on the protective layer and obtaining the magnetic recording medium.
[0219] (film thickness measurement) The thickness of the lubricating layer of each of the magnetic recording media thus obtained in Examples 1 to 18 and Comparative Examples 1 to 5 was measured using an FT-IR (product name: Nicolet iS50, manufactured by Thermo Fisher Scientific Co.) The results are shown in Table 4.
[0220] [Table 4]
[0221] Next, the magnetic recording media of Examples 1 to 18 and Comparative Examples 1 to 5 were subjected to the following wear resistance test.
[0222] (Wear resistance test) Using a pin-on-disk type friction and wear tester, an alumina ball with a diameter of 2 mm was slid as a contact on the lubricating layer of the magnetic recording medium at a load of 40 gf and a sliding speed of 0.25 m / sec to measure the friction coefficient of the surface of the lubricating layer. Then, the sliding time until the friction coefficient of the surface of the lubricating layer suddenly increased was measured. The sliding time until the friction coefficient suddenly increased was measured four times for the lubricating layer of each magnetic recording medium, and the average value (time) was used as an index of the wear resistance of the lubricant coating. The results of the magnetic recording media using the compounds of Examples 1 to 18 and Comparative Examples 1 to 5 are shown in Table 4. The evaluation of the friction coefficient increase time was as follows.
[0223] ◎(Excellent): 650sec or more ○(Good): 550 sec or more, less than 650 sec △ (OK): 450 sec or more, less than 550 sec
[0224] The time until the friction coefficient increases sharply can be used as an index of the wear resistance of the lubricating layer for the following reason. The lubricating layer of the magnetic recording medium wears away as the magnetic recording medium is used, and when the lubricating layer is worn away, the contact and the protective layer come into direct contact, causing a sharp increase in the friction coefficient. The time until the friction coefficient increases sharply is thought to be correlated with the friction test.
[0225] As shown in Table 4, the magnetic recording media of Examples 1 to 18 had a longer sliding time until the friction coefficient increased sharply and had better wear resistance than the magnetic recording media of Comparative Examples 1 to 5. In addition, from the results of Examples 1 to 8, R 5 R 6 It was confirmed that when N- is a pyrrolidine group or a morpholine group, a lubricating layer having particularly excellent wear resistance can be obtained.
[0226] (Chemical Resistance Test) The following evaluation method was used to investigate the contamination of magnetic recording media by environmental substances that generate contaminants in a high-temperature environment. In the evaluation method described below, Si ions were used as the environmental substances, and the amount of Si adsorption was measured as the amount of contaminants that contaminate the magnetic recording media and are generated by the environmental substances.
[0227] Specifically, the magnetic recording medium to be evaluated was kept in the presence of siloxane-based Si rubber for 240 hours in a high-temperature environment of 85°C and 0% humidity. The amount of Si adsorption on the surface of the magnetic recording medium was then analyzed and measured using secondary ion mass spectrometry (SIMS), and the degree of contamination by Si ions was evaluated as the amount of Si adsorption. The amount of Si adsorption was evaluated using a numerical value when the result of Comparative Example 1 was set to 1.00. The results are shown in Table 4. The smaller the numerical value, the better the chemical resistance.
[0228] As shown in Table 4, it was clear that the magnetic recording media of Examples 1 to 18 had a smaller amount of Si adsorption and were less susceptible to contamination by environmental substances in a high-temperature environment, compared to the magnetic recording media of Comparative Examples 1 to 5. In addition, from the results of Examples 1 to 8, R 4 It was confirmed that when g in formula (7) is 2, a lubricating layer having better chemical resistance can be obtained than when g is 1.
[0229] Moreover, a comprehensive evaluation was performed on the compounds and magnetic recording media of Examples 1 to 18 and Comparative Examples 1 to 5 based on the following criteria. The results are shown in Table 4. ◎ (Excellent): The friction coefficient increase time was evaluated as ◎ (Excellent) and the amount of Si adsorption was less than 0.51. ◯ (Good): The friction coefficient increase time was evaluated as ◎ (Excellent) or ◯ (Good), and the amount of Si adsorption was less than 1.01 △ (passable): The evaluation of the friction coefficient increase time is △ (passable) and the amount of Si adsorption is less than 1.01 × (unacceptable): Evaluation of friction coefficient increase time is △ (acceptable) and the amount of Si adsorption is 1.01 or more
[0230] As shown in Table 4, the magnetic recording media of Examples 1 to 18 using the compound represented by formula (1) were given an overall rating of ⊚ (excellent) or ◯ (good), and excellent wear resistance and chemical resistance were obtained. In contrast, the overall evaluation of Comparative Example 1 was △ (passable), and the overall evaluations of Comparative Examples 2 to 5 were × (unacceptable).
[0231] More specifically, R in formula (1) 1 The structure of (R in formula (2) 5 R 6 In Comparative Example 1, in which a compound containing a pyridine group was used instead of N-), the results of the abrasion resistance test and the chemical resistance test were inferior to those of Examples 1-18. From this, R in Eq. (1) 1 The structure of (R in formula (2) 5 R 6 It was confirmed that N-) contributes to improving the wear resistance and chemical resistance of the lubricating layer.
[0232] In addition, R in formula (1) 2 In Comparative Example 2, in which a compound not having the structure was used, the results of the abrasion resistance test and the chemical resistance test were inferior to those of Examples 1 to 18. From this, it is considered that the R 2 It was confirmed that this structure contributes to improving the wear resistance and chemical resistance of the lubricating layer.
[0233] In addition, the PFPE chain has a structure in which a tertiary amine is bonded to both ends of the PFPE chain via a divalent linking group having an ether bond and a hydroxyl group, and R 1 In formula (2), -(CH2) a The structure of -O- and R 4 In Comparative Example 3, in which a compound not having the above structure was used, the results of the abrasion resistance test and the chemical resistance test were inferior to those of Examples 1-18. In addition, the PFPE chain has a structure in which a tertiary amine having a hydroxyl group is bonded to both ends thereof, and R 1 In formula (2), -(CH2) a -O- structure, R2 The structure of and R 4 In Comparative Example 4, in which a compound not having the above structure was used, the results of the abrasion resistance test and the chemical resistance test were inferior to those of Examples 1-18. Furthermore, among Comparative Examples 1 to 5, Comparative Examples 3 and 4 had particularly large amounts of Si adsorption and showed poor results in the chemical resistance test.
[0234] In addition, R in formula (1) 4 In Comparative Example 5, in which a compound having two hydroxyl groups bonded to different carbon atoms at one end of the PFPE chain and a terminal group in which the carbon atoms to which the hydroxyl groups are bonded are bonded to each other was used instead of the structure above, the results of the abrasion resistance test and the chemical resistance test were poor. From this, R in Eq. (1) 4 It was confirmed that this structure contributes to improving the wear resistance and chemical resistance of the lubricating layer. [Industrial Applicability]
[0235] The present invention provides a fluorine-containing ether compound suitable as a material for a lubricant for a magnetic recording medium, which is capable of forming a lubricating layer having excellent chemical resistance and abrasion resistance even when the thickness is reduced. By using a lubricant for magnetic recording media containing the fluorinated ether compound of the present invention, a lubricating layer having excellent abrasion resistance and chemical resistance can be formed even if it is thin. [Explanation of symbols]
[0236] 10 magnetic recording medium, 11 substrate, 12 adhesion layer, 13 soft magnetic layer, 14 first underlayer, 15 second underlayer, 16 magnetic layer, 17 protective layer, and 18 lubricating layer.
Claims
1. A fluorine-containing ether compound represented by the following formula (1): R 1 -R 2 -CH 2 -R 3 -CH 2 -R 4 (1) (In formula (1), R 3 is a perfluoropolyether chain; R 1 is represented by the following formula (2), in which a is an integer of 2 or 3, and in formula (2), R 5 and R 6 are the same or different substituents, R 5 and R 6 are each independently a saturated aliphatic group having 1 to 4 carbon atoms, or in the formula (2), R 5 R 6 N- is any one group selected from a pyrrolidine group, a piperidine group, a morpholine group, and a hexamethyleneimine group; R 2 is represented by the following formula (3), where b is an integer of 1 to 3; R 4 is an end group of any one of the following formulas (7) to (10). 【Chemistry 1】 【Chemistry 2】 (In formula (7), g represents an integer of 1 to 2, and h represents an integer of 1 to 5.) (In formula (8), i represents an integer of 2 to 5.) (In formula (9), j represents an integer of 1 to 5.) (In formula (10), k represents an integer of 1 or 2, and l represents an integer of 1 or 2.)
2. R in the formula (2) 5 R 6 2. The fluorine-containing ether compound according to claim 1, wherein N- is a dimethylamino group or a diethylamino group.
3. The R 3 The fluorine-containing ether compound according to claim 1 or 2, wherein is represented by any one of the following formulas (4) to (6): -CF 2 O-(CF 2 CF 2 O) c -(CF 2 O) d -CF 2 - (4) (In formula (4), c and d each represent an average degree of polymerization and are from 0 to 30. However, c and d cannot be 0 at the same time.) -CF(CF 3 )-(OCF(CF 3 )CF 2 ) e -OCF(CF 3 )- (5) (In formula (5), e represents the average degree of polymerization and is 0.1 to 30.) -CF 2 CF 2 O-(CF 2 CF 2 CF 2 O) f -CF 2 CF 2 - (6) (In formula (6), f represents the average degree of polymerization and is 0.1 to 30.)
4. The fluorine-containing ether compound according to any one of claims 1 to 3, having a number average molecular weight in the range of 500 to 10,000.
5. The fluorine-containing ether compound according to any one of claims 1 to 4, wherein the compound represented by formula (1) is any one of compounds represented by the following formulas (A) to (D), (N) and (O): 【Chemistry 3】 (In formula (A), ma and na represent average degrees of polymerization, ma representing 1 to 30, and na representing 0 to 30.) (In formula (B), mb and nb represent average degrees of polymerization, mb represents 1 to 30, and nb represents 0 to 30.) (In formula (C), mc and nc represent average degrees of polymerization, mc represents 1 to 30, and nc represents 0 to 30.) (In formula (D), md and nd represent average degrees of polymerization, md represents 1 to 30, and nd represents 0 to 30.) (In formula (N), mn and nn represent average degrees of polymerization, mn represents 1 to 30, and nn represents 0 to 30.) (In formula (O), mo and no represent average degrees of polymerization, mo representing 1 to 30, and no representing 0 to 30.)
6. A lubricant for magnetic recording media, comprising the fluorine-containing ether compound according to any one of claims 1 to 5.
7. A magnetic recording medium comprising at least a magnetic layer, a protective layer, and a lubricating layer provided in this order on a substrate, 6. A magnetic recording medium, comprising the lubricating layer comprising the fluorine-containing ether compound according to claim 1.
8. 8. The magnetic recording medium according to claim 7, wherein the average thickness of the lubricating layer is from 0.5 nm to 2 nm.
Citation Information
Patent Citations
Polyether compound and magnetic recording medium
JP1999131083A
Lubricant, magnetic recording medium and manufacturing method of magnetic recording medium
JP2006225572A
Perfluoropolyether-containing amine, and surfactant
JP2008120714A
Liquid lubricant, magnetic recording medium using the same, and method for manufacturing the same
JP4099860B2
Perfluoropolyether compound and lubricant and magnetic disk using same
WO2004031261A1